ESTABLISHING A YEARLONG TEACHER RESIDENCY a roadmap for transforming. - Sloan, Christopher J.; Beal, Sarah ([S.l.] : ROUTLEDGE, 2025)
This book outlines a model for a teacher residency and how to establish a yearlong residency within an educator preparation program. It describes the four-year experiences of stakeholders at Tarleton State University but can be used as a step-by-step guide, in whole or in part, to transforming teacher preparation at any university. After a brief description of the traditional clinical model and why a university may look to make a change, the book offers a roadmap for the entire process of moving to a residency model. The chapters provide detailed explanations of how to build mutually beneficial partnerships with school districts, utilize co-teaching models, and create revised roles for cooperating teachers, teacher-residents, university and district leaders, and site coordinators. Contributing authors also cover change processes (successes and failures), funding models, scaling, sustainability, data collection, and evidence of effectiveness. Based on Tarleton's recognition as one of the fastest-scaling residency programs and most complete transformations to date, the tools presented offer any teacher prep program the opportunity to make the leap to a residency model. This resource is also ideal for school district leaders seeking guidance on building or enhancing existing partnerships with universities, and for in-service teachers interested in discovering new co-teaching models.
Keywords: Teachers -- Training of; EDUCATION / General; EDUCATION / Organizations & Institutions; EDUCATION / Professional Development